Coherent Response of Antarctic Intermediate Water and Atlantic Meridional Overturning Circulation During the Last Deglaciation: Reconciling Contrasting Neodymium Isotope Reconstructions From the Tropical Atlantic. (24th October 2017) - Gu, Sifan; Liu, Zhengyu; Zhang, Jiaxu; Rempfer, Johannes; Joos, Fortunat; Oppo, Delia W.
Abstract: Antarctic Intermediate Water (AAIW) plays important roles in the global climate system and the global ocean nutrient and carbon cycles. However, it is unclear how AAIW responds to global climate changes. In particular, neodymium isotopic composition ( ε Nd ) reconstructions from different locations from the tropical Atlantic have led to a debate on the relationship between northward penetration of AAIW into the tropical Atlantic and the Atlantic meridional overturning circulation (AMOC) variability during the last deglaciation. We resolve this controversy by studying the transient oceanic evolution during the last deglaciation using a neodymium‐enabled ocean model. Our results suggest a coherent response of AAIW and AMOC: when AMOC weakens, the northward penetration and transport of AAIW decrease while its depth and thickness increase. Our study highlights that as part of the return flow of the North Atlantic Deep Water, the northward penetration of AAIW in the Atlantic is determined predominately by AMOC intensity. Moreover, the inconsistency among different tropical Atlantic ε Nd reconstructions is reconciled by considering their corresponding core locations and depths, which were influenced by different water masses in the past. The very radiogenic water from the bottom of the Gulf of Mexico and the Caribbean Sea, which was previously overlooked in the interpretations of deglacial ε Nd variability, can be transported to shallow layers during active AMOC and modulates ε Nd in the tropical Atlantic. Changes in the AAIW core depth must also be considered. Thus, interpretation of ε Nd reconstructions from the tropical Atlantic is more complicated than suggested in previous studies. Key Points: Antarctic Intermediate Water northward penetration is controlled by the Atlantic meridional overturning circulation strength Atlantic Intermediate Water becomes deeper and thicker during weaker Atlantic meridional overturning circulation period The contradictory tropical Atlantic ε Nd reconstructions are due to the site location and depth and the influence of different water masses